The Meaning of the Colour Blue - Chahal, Taina (UnderCurrents: Journal of Critical Environmental Studies, 2004)
The language of the birds outside my bedroom window has to compete with the sound of traffic seeping through the brick walls that becomes a part of my day, like the canned music that fills my ear when I’m once again waiting for a real voice on the telephone instead of a “press three” for hours of operation.